Effect Isolation and identification of Listeria monocytogenes from aborted women with studing of its pathogenic - Abdalla, M. S.; AL-Khatib, G. M.; Alwan, M. J. (The Iraqi Journal of Veterinary Medicine, 2004)
The isolation and identification of the bacterium L.monocytogenes among abortion in pregnant women were investigated in this research. One hundred and fifty samples including placental tissue and maternal blood were randomly collected from cases of abortion from AL-Habibia Teaching Hospital and AL-Yarmuk Teaching Hospital. These samples were taken from patients in 16 - 45 years of age. Listeria monocytogenes was isolated from three cases only, two of them from AL-Habibia Teaching Hospital ,while the other one from AL-yarmuk Teaching Hospital. Their gestational age were 22 , 24 , and 28 weeks. Bacterial isolation was done by using routin and specific culture media and two methods for enrichment were preformed. The biological and biochemical properties of the isolates as well as the pathogenicity of L.monocytogenes in mice were described in the original paper. Infected mice were died after 2 - 5 days post inoculation. The histopathological changes were acute suppurative inflammation in the begining « later on chronic granulomatous reaction were developed , within internal organs